2019
DOI: 10.24940/theijst/2019/v7/i11/st1911-018
|View full text |Cite
|
Sign up to set email alerts
|

Health System Factors That Influence Health Seeking Behavior Associated With Prostatism among Men above 40 Years in Nyamira County

Abstract: Prostatism refers to obstruction of the bladder neck due to an enlargement of the prostate as men ages leading to urinary difficulties (Jong et al., 2014). Prostatism results to development of nodules which are larger blocking the urethrahence increasing urine flow resistance. The condition is manifested by irritative symptoms (sensory urgency, urgency, frequency plus urgent incontinence) and obstructive (double voiding, decreased stream, urinary retention, terminal dribbling and hesitancy (Cunningham, 2013). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“… 24 , 39 Matoke also found that fear, cost and embarrassment were barriers to seeking treatment for prostatism. 40 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 24 , 39 Matoke also found that fear, cost and embarrassment were barriers to seeking treatment for prostatism. 40 …”
Section: Discussionmentioning
confidence: 99%
“…24,39 Matoke also found that fear, cost and embarrassment were barriers to seeking treatment for prostatism. 40 Studies to determine the correlation between PV and IPSS had always yielded varying results. Basawaraj and associates 41 found a positive correlation between PV and IPSS (r = 0.40; p = 0.001).…”
Section: Ipssmentioning
confidence: 99%
“…The severity of depression was categorised according to the PHQ-9 cut-off points as shown in Table 2. Out of the study population of 308, 39.90% had mild depression (5-9), 2.30% had moderate depression (10-14) and 0.30% had moderately severe (15)(16)(17)(18)(19) or severe depression (20-27). The majority of those depressed had mild symptoms.…”
Section: Prevalence Of Depressive Symptoms Among Benign Prostatic Enl...mentioning
confidence: 99%
“…13,14,15 There is a paucity of studies that have focused on sBPE and its interplay with depression in the African context and more specifically in Kenya. 16 This is especially important given the unique socio-cultural, socio-economic and health system factors experienced within the African and Kenyan context. Social and cultural environments have a demonstrable link with the prognosis of various diseases.…”
Section: Introductionmentioning
confidence: 99%
“…7 Study In Nyamira County in Kenya, showed 87.9% of respondents had never sought medical help. 8 The objective of this study was determine influence of health institution related factors influencing health seeking behaviors among male patients suffering from LUTS attending surgical outpatient clinic at Meru county referral hospital Kenya.…”
Section: Introductionmentioning
confidence: 99%